2015
DOI: 10.1063/1.4922852
|View full text |Cite
|
Sign up to set email alerts
|

3D-printed slit nozzles for Fourier transform microwave spectroscopy

Abstract: 3D printing is a new technology whose applications are only beginning to be explored. In this report, we describe the application of 3D printing to the design and construction of supersonic nozzles. Nozzles can be created for $0.50 or less, and the ease and low cost can facilitate the optimization of nozzle performance for the needs of any particular experiment. The efficacy of a variety of designs is assessed by examining rotational spectra of OCS (carbonyl sulfide) and Ar-OCS using a Fourier transform microw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…Rotational spectra of the triflic acid hydrates were collected using a combined cavity and chirped-pulse Fourier transform microwave spectrometer, details of which have been given elsewhere. , Transition frequencies obtained on the chirped-pulse system were typically accurate to ∼12 kHz, while those obtained in the cavity mode of the spectrometer were accurate to ∼3 kHz. In the case of di-deuterated isotopologues, however, the dense deuterium hyperfine structure decreased the measurement accuracy such that only approximate line centers could be obtained.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…Rotational spectra of the triflic acid hydrates were collected using a combined cavity and chirped-pulse Fourier transform microwave spectrometer, details of which have been given elsewhere. , Transition frequencies obtained on the chirped-pulse system were typically accurate to ∼12 kHz, while those obtained in the cavity mode of the spectrometer were accurate to ∼3 kHz. In the case of di-deuterated isotopologues, however, the dense deuterium hyperfine structure decreased the measurement accuracy such that only approximate line centers could be obtained.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…The rotational spectrum of 3,5-difluoropyridine•••CO 2 was obtained using a Fourier transform microwave spectrometer with tandem cavity [9] and chirped-pulse [10] capabilities. Details of the instrument have been provided elsewhere [11,12]. Briefly, the cavity mode of the spectrometer operates along one axis and the chirped-pulse mode along an orthogonal axis.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…Initially, a chirped pulse spectrum from 6-18 GHz was taken using our standard circular 0.8 mm orifice nozzle, but the number of observed transitions was insufficient to make definitive spectral assignments. Using a newly developed 3D-printed nozzle that terminates in a 1.25 x 0.0085 slit [12], however, a sufficient number of rotational transitions were observed that spectral assignments could be made and an initial rough fit generated. Figure 1 shows a comparison between the chirped-pulse spectra with the traditional nozzle and the slit nozzle.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…While developments in accessible 3D printing and microcontrollers has seen widespread use amongst amateur users, these technologies have only seen limited application within the scientific community. Two examples of scientific equipment manufactured with 3D printing include static optical components[ 5 ] and supersonic expansion nozzles[ 6 ]. However, these are both simple products without moving parts.…”
Section: Introductionmentioning
confidence: 99%
“…The overall structure forms a paper several microns thick ( Fig 1a ) with lamellae that are highly interconnected in a honeycomb-like structure as pictured in Fig 1b . The GO papers used in this study are manufactured using a process called vacuum-assisted self-assembly[ 2 , 6 , 13 ] (VASA). The process involves the suspension of GO nano-sheets in an aqueous solution and filtering the solution with the assistance of a vacuum pump to remove the water and create GO paper.…”
Section: Introductionmentioning
confidence: 99%